Prevalence of Type I Allergy to Latex and Type IV Allergy to Rubber Additives in Turkish Healthcare Workers - Hasan Aksoy; Necmettin Akdeniz; Fatma Karakurt (Mattioli1885, 2023)
Introduction: Glove-induced dermatoses are frequently seen among healthcare workers (HCWs) and are often mistakenly defined as latex allergy. Objectives: To determine the prevalences of (i) the symptoms of immediate type hypersensitivity reactions, (ii) the symptoms of hand eczema, (iii) latex sensitization detected using SPT, and (iv) contact hypersensitivity to rubber additives or glove pieces detected using patch test, in Turkish HCWs. Methods: Ninety-eight HCWs were included in the study. All subjects completed a questionnaire. All participants were skin prick tested for latex, and foods previously identified as concomitant allergens in latex-sensitive individuals; patch tested for 7 rubber additives, 3 additional haptens, and glove pieces. Results: The mean age was 32.1 (± 9.4) years, and 71 (72.4%) participants were nurses. Eighty-four (85.7%) subjects had a history of mucocutaneous symptoms of immediate-type hypersensitivity occurring within the first 24 hours after latex glove contact, while 9 (9.2%) subjects demonstrated SPT positivity for latex. Eighty (81.6%) subjects had a history of glove-induced hand eczema symptoms, while patch test positivity for the rubber additives or glove pieces was in 17.3%. Conclusions: About one-tenth of those with a history of glove-induced type I hypersensitivity symptoms had true latex allergy, and one-quarter of those with a history of glove-related hand eczema symptoms had contact hypersensitivity to glove products. Therefore, rote avoidance of latex use is generally ineffective in the management of glove-related skin complaints. Individual measures should focus on reducing the use of soaps and disinfectants, and promoting the use of moisturizers, rather than glove choice.